HUBUNGAN INDEKS MASSA TUBUH DENGAN ANKLE RANGE OF MOTION PADA SISWA SMK KESEHATAN BHAKTI INSANI DEPOK - Rizka Maulidha, (2022)
Background : Range of motion (ROM) is the normal limit of joint angular motion. One of the factors that can affect a person's ROM is weight. A person's weight can be categorized as less, normal, more, or obese based on a parameter commonly known as BMI, weight (kg) divided by height squared divided by square meters (m2). The purpose of this study was to determine if there was a relationship between the body mass index (BMI) with ankle range of motion (ROM) in students of SMK Kesehatan Bhakti Insani Depok. Design: In this study, a cross-section approach-based quantitative correlation design was used in a total of 108 student samples from SMK Kesehatan Bhakti Insani Depok. The parameter used to measure the ankle ROM is the goniometer. Results: it was found that most Bhakti Insani Health Depok students had normal BMI and ankle ROM values. This study used SPSS 23 and the results obtained p = 0.01 conclusion there is a non-unidirectional relationship between BMI and ankle ROM.